Friction relations for the many-sphere Oseen hydrodynamic interactions - Pieńkowska, I. (Archives of Mechanics, 1996)
The paper concerns weak inertia effects arising in the many-sphere hydrodynamic interactions. Rigid spheres are held fixed in an incompressible fluid flowing with uniform velocity U at infinity. The friction relations, up to the contributions of the order O(Re), where Re is the Reynolds number, are considered on the basis of the Oseen equations.